Loss of DNA-dependent dimerization of the transcription factor SOX9 as a cause for campomelic dysplasia - Sock, Elisabeth; Wegner, Michael; et al. (Human Molecular Genetics, 2003)
Campomelic dysplasia (CD) is a semilethal osteochondrodysplasia, characterized by skeletal anomalies that include bending of the long bones, and by XY sex reversal. CD results from haploinsufficiency for the transcription factor SOX9, a key regulator at various steps of cartilage differentiation and of early testis development. Two functional domains are so far recognized for SOX9, a high-mobility group (HMG) DNA-binding domain and a C-terminal transactivation domain. We present two CD patients with de novo mutations in a conserved region preceding the HMG domain. A long-term survivor with the acampomelic form of CD has an A76E amino acid substitution, while a severely affected CD patient had an in-frame deletion of amino acid residues 66-75. The conserved domain has been shown to function in the related transcription factor SOX10 as a DNA-dependent dimerization domain. We show that, like SOX10, SOX9 also binds cooperatively as a dimer to response elements in regulatory regions of some target genes such as the cartilage genes Col11a2 and CD-Rap. Dimerization and the resulting capacity to activate promoters via dimeric binding sites is lost in both mutant SOX9 proteins while other features involved in SOX9 function remained unaltered. These findings establish the dimerization domain as the third domain essential for SOX9 function during chondrogenesis.
UnivIS-Import:2015-03-09:Pub.2003.med.IB.LPCIPDBI.lossof